Design and development of inner dispersion system of magneto-rheological (MR) damper - Mohammad Abdul Aziz (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Magnetorheological (MR) dampers are widely used for vehicle suspension systems, and MR fluid sedimentation is an indispensable problem of MR dampers. During field off and field on damping operation MR fluid sediments on the bottom of MR damper. The sedimentation of the MR fluid leads to poor dispersion of the fluid in the damper which in turn reduces performance of the damper. The aim of this research is to design and develop bypass MR damper (BMRD) through improving dispersion of MR fluid, to increase performance of the MR damper. This study presents the characteristics of BMRD inside piston arrangements. The BMRD developed under this research consists of a piston which contains holes and coil case cylinder, coil windings, piston rod, piston head cover, bobbin, one cylindrical tube and external bypass tube for bypassing MR fluids. An annular valve has been made active inside the piston for controlling the damping force. The BMRD was simulated using Comsol Multiphysics simulation software. The model used for the simulation was a 2-D axisymmetric model. The magnetic flux propagation of the BMRD predicted the efficiency and damping force generated in the damper. The proposed MR damper piston and magnetic coil arrangement produces higher dynamic range and higher piston velocity for vibration mitigation. The analysis of bypass MR damper characterized by Bingham-plastic model and the shaft/piston velocity as stoking load, dynamic range, and equivalent damping. The theoretical and hydro-mechanical model for the BMRD was then proposed according to the nonlinear Bingham-plastic fluid model. The prototype model was then fabricated and tested using a Universal Testing Machine (UTM) where both valve & shear mode experimental operation were done using BMRD. The results of valve mode BMRD experiments were compared with shear mode BMRD experiments. The results obtained from Bypass MR damper is found to be similar to the original Lord Corporation MR Damper. The lowest and highest forces found from the shear mode experiments were 189.8097 N and 3700 N while in the valve mode experiment the lowest and highest forces were 800 N and 5800 N respectively.